2020
DOI: 10.31703/gmcr.2020(v-ii).02
|View full text |Cite
|
Sign up to set email alerts
|

Role of Print Media During COVID-19: A Content Analysis of Daily Mashriq and Daily Aaj in Pakistan

Abstract: Print media plays a key role in raising awareness among people and in the public understanding of various issues. This study discusses the role the print media during COVID-19 pandemic how the print media raises awareness among people in the contagion. Using a quantitative method, the researchers analysed the contents of two leading newspapers of Khyber Pakhtunkhwa, daily Mashriq and Daily Aaj. The study then achieved the results regarding how they reported the stories in various dimensions such as awareness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…mass media including print, television and social media. Among the various sources of mass communication, print media is the oldest one as individuals from Pakistan still found the recognized print media outlets as reliable and trustworthy source of information as compared to television and social media (Shahid, Istimraj & Nawaz, 2020).Additionally, it is found that media organizations played a pro-active role in disseminating the information during major health crisis (Arif, Mahmood & Mughal Anwar, 2020). Media outlets determine the news content as well as the scale of priority which is given to particular aspect of the story (Arif & Hassan, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…mass media including print, television and social media. Among the various sources of mass communication, print media is the oldest one as individuals from Pakistan still found the recognized print media outlets as reliable and trustworthy source of information as compared to television and social media (Shahid, Istimraj & Nawaz, 2020).Additionally, it is found that media organizations played a pro-active role in disseminating the information during major health crisis (Arif, Mahmood & Mughal Anwar, 2020). Media outlets determine the news content as well as the scale of priority which is given to particular aspect of the story (Arif & Hassan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Media outlets determine the news content as well as the scale of priority which is given to particular aspect of the story (Arif & Hassan, 2020). Along with potential role of media, it is found that factors such as social, political and economic situation of a country also provided context for news framing in choosing that which aspect of the story is to highlight and which ones to exclude (Mutua & Ong'ong'a, 2020).There are evidences suggesting that during major health crisis, news framing become a prominent aspect as particular news frames not only effects the public discourse but also helps in communicating the interventions effectively (Gislason, 2013;Shahid et al, 2020).These media frames were introduced by Neuman Russel and his colleagues that are economic, conflict, powerlessness, human interest, attribution of responsibility and moral values. (Neuman, Just and Crigler, 1992).Later, Valkenburg and Sematko (1999) employed Neuman et al frames and they were also able to form a scale to evaluate the frames of attribution of responsibility, conflict, morality, economic consequence and human interest.Among these frames most suitable ones are used for the paper, that are discussed later in this study.…”
Section: Introductionmentioning
confidence: 99%